La huella de Cervantes en la obra de Flaubert - Patricia Martínez García (Mélanges de la Casa de Velázquez)
The admiration that Flaubert always evinced for the work of Cervantes, which he described in his Correspondence as the book of «origins», is well known. The example of Don Quixote may well lie behind Flaubert’s anti-novelistic and metafictional realism in the sense that it constitutes a critique of romantic literature and an ironic deconstruction of its clichés and rhetorical conventions. From that standpoint Flaubert’s work as a whole is consistent with Cervantes’ premises: disillusionment, and the reader’s disappointment in his dealings with fiction. Such anti-novelistic criticism is particularly evident in Madame Bovary. Following Cervantes’ lead, Flaubert creates a poetics of disillusionment, discernible in the thematic elements of his fiction and also in his narrative discourse and textual structure, which subtly deconstructs the fabrications of novelistic romanticism, exposing the tricks and artifices and putting on display the falsehood of all fiction.